The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1523-1747.2002.19627.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Inhibits the Production of Interferon-induced Protein of 10 kDa in Human Squamous Cell Carcinoma and Melanoma

Abstract: Interferon-induced protein of (IP-10) inhibits tumor progression. Tumor cells can produce interferon-induced protein of IP-10 in response to interferon-g. Histamine in the vicinity of tumor cells may sustain the tumor progression. We examined the in vitro effects of histamine on interferon-induced protein of IP-10 production in human squamous cell carcinoma and melanoma. Histamine suppressed interferon-g-mediated interferon-induced protein of IP-10 secretion and mRNA expression in SV40-transformed keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Inhibition of IP-10 production was mediated solely by H 2 receptors. This is consistent with a previous study showing the involvement of H 2 receptors and cAMP in the regulation of IP-10 secretion (36). In contrast, modulation of MIG was also mediated by H 1 and H 3 histamine receptors whereas RANTES secretion was mediated by H 2 Studies on the possible role of CXCL9/MIG in inflammatory responses in the lung showed a strong association between MIG levels and the regulation of allergic airway inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of IP-10 production was mediated solely by H 2 receptors. This is consistent with a previous study showing the involvement of H 2 receptors and cAMP in the regulation of IP-10 secretion (36). In contrast, modulation of MIG was also mediated by H 1 and H 3 histamine receptors whereas RANTES secretion was mediated by H 2 Studies on the possible role of CXCL9/MIG in inflammatory responses in the lung showed a strong association between MIG levels and the regulation of allergic airway inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…This effect was mediated primarily by the H2 receptor and suggests that histamine may suppress antitumor immune responses. 26 We have also shown that levocetirizine very efficiently blocks all of the proinflammatory actions of histamine on keratinocytes. In contrast, the H2 antagonist cimetidine did not inhibit these inflammatory actions of histamine, as previously observed.…”
Section: Discussionmentioning
confidence: 63%
“…TNF␣ induces IP10 secretion in mast cells but through NFkB and p38-MAPK pathways, not involving ERK, 21 whereas IFN␥-induced IP10 synthesis is suppressed by Stat1 inhibition. 22 The anti-inflammatory effects of PPAR␥ ligands, evaluated as the ability of TZD to inhibit IFN␥ proinflammatory effects, have been previously investigated in vasculopathies. 5 Although currently published studies suggest that the antiinflammatory action of TZD can be mediated both in vivo [23][24][25] and in vitro 9 by their ability to interfere with the transcriptional activity of NFB, the intracellular mechanisms underlying such effects might not be yet fully clarified.…”
Section: Discussionmentioning
confidence: 99%